Major histocompatibility complex and other allergy-related candidate genes associated with insect bite hypersensitivity in Icelandic horses - Klumplerova, Marie; Vychodilova, Leona; Bobrova, Olga; Cvanova, Michaela; Futas, Jan; Janova, Eva; Vyskocil, Mirko; Vrtkova, Irena; Putnova, Lenka; Dusek, Ladislav; Marti, Eliane; Horin, Petr (Molecular biology reports, 2013)
Insect bite hypersensitivity (IBH) is an allergic dermatitis of horses caused by bites of insects. IBH is a multifactorial disease with contribution of genetic and environmental factors. Candidate gene association analysis of IBH was performed in a group of 89 Icelandic horses all born in Iceland and imported to Europe. Horses were classified in IBH-affected and non-affected based on clinical signs and history of recurrent dermatitis, and on the results of an in vitro sulfidoleukotriene (sLT)-release assay with Culicoides nubeculosus and Simulium vittatum extract. Different genetic markers were tested for association with IBH by the Fisher's exact test. The effect of the major histocompatibility complex (MHC) gene region was studied by genotyping five microsatellites spanning the MHC region (COR112, COR113, COR114, UM011 and UMN-JH34-2), and exon 2 polymorphisms of the class II Eqca-DRA gene. Associations with Eqca-DRA and COR113 were identified (p < 0.05). In addition, a panel of 20 single nucleotide polymorphisms (SNPs) in 17 candidate allergy-related genes was tested. During the initial screen, no marker from the panel was significantly (p < 0.05) associated with IBH. Five SNPs associated with IBH at p < 0.10 were therefore used for analysis of combined genotypes. Out of them, SNPs located in the genes coding for the CD14 receptor (CD14), interleukin 23 receptor (IL23R), thymic stromal lymphopoietin (TSLP) and transforming growth factor beta 3 (TGFB3) molecules were associated with IBH as parts of complex genotypes. These results are supported by similar associations and by expression data from different horse populations and from human studies.
Keywords: Major Histocompatibility Complex; Horses; Insect Bites and Stings; zvířata; hlavní histokompatibilní komplex; Island; Simuliidae; Hypersensitivity; Iceland; Ceratopogonidae; koně; Dermatitis; dermatitida; alergie; kousnutí a bodnutí hmyzem; Animals